Between adat law and living law: an illusion of customary law incorporation into Indonesia penal system. Issue 2 (4th May 2021) - Utama, Tody Sasmitha Jiwa
Abstract: The initiative to recognize and incorporate customary law into the state system is now a ubiquitous phenomenon. However, how and for what purposes such incorporation has to be performed is still a heated debate. Using the case of the Indonesian Bill of Criminal Code (BCC), this article examines how the government uses its law-making power to utilize customary law (adat law) and the legal and political benefits the state could earn from such utilization. I argue that, by constructing adat law as 'living law' and using it as the basis for criminal conviction, the BCC has continued its romantic, but legalistic, approach in managing legal pluralism. This article envisions that such incorporation will freeze the dynamic character of adat law, allowing the state to entrench its domination and create a false sense of security in responding to Indonesia's legal pluralism challenges. Therefore, the state recognition of adat law can distort and undermined adat law as an empirical phenomenon.